2006
DOI: 10.2353/jmoldx.2006.050118
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Fluorescence in Situ Hybridization Assay for the Detection of Dysplasia and Adenocarcinoma in Barrett's Esophagus

Abstract: The goal of this study was to identify a set of fluorescence in situ hybridization probes for the detection of dysplasia and adenocarcinoma in patients with Barrett's esophagus. We examined 170 brushing specimens from 138 patients with Barrett's esophagus or a history of Barrett's esophagus using fluorescence in situ hybridization with probes to 5p15, 5q21-22, centromere 7, 7p12, 8q24.12-13, centromere 9, 9p21, centromere 17, 17p13.1, 17q11.2-12, 20q13.2, and centromere Y. Receiver-operator curves were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 29 publications
(27 reference statements)
2
57
0
Order By: Relevance
“…Their combined frequencies significantly increase with increasing stage of dysplasia and have high incidence in esophageal adenocarcinoma. These findings correspond well with comparative genomic hybridization and FISH studies examining the same chromosomal regions (23,28,32). The detected gains in our study may reflect aneuploidy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Their combined frequencies significantly increase with increasing stage of dysplasia and have high incidence in esophageal adenocarcinoma. These findings correspond well with comparative genomic hybridization and FISH studies examining the same chromosomal regions (23,28,32). The detected gains in our study may reflect aneuploidy.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, we clearly found low amplification of the EGFR locus in one of the high-grade dysplasia case. In a recent FISH study, gains of the EGFR locus were reported, but amplification was not described in high-grade dysplasia cases (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies are conflicting as to how much additional information can be obtained from cytological examination. However, the use of new genetic markers, such as fluorescent in situ hybridization may be promising in increasing the clinical utility of brush cytology (41).…”
Section: The Management Of Dysplasiamentioning
confidence: 99%
“…Moreover, use of FFPE tissue allows retrospective sample analysis [31]. Exploration of p16 (9p21) by FISH is successfully utilized for EAC detection [32]. We found prominent loss of p16 gene by means of FISH.…”
Section: Discussionmentioning
confidence: 94%